Leptolysin, a Leptospira secreted metalloprotease of the pappalysin family with broad-spectrum activity - Courrol, Daniella dos Santos; Silva, Cristiane Castilho Fernandes da; Prado, Luan Gavião; Chura-Chambi, Rosa Maria; Morganti, Ligia; de Souza, Gisele Oliveira; Heinemann, Marcos Bryan; Isaac, Lourdes; Conte, Fernando Paiva; Portaro, Fernanda Calheta Vieira; Rodrigues-da-Silva, Rodrigo Nunes; Barbosa, Angela Silva (Frontiers in Cellular and Infection Microbiology, 2022)
Extracellular proteolytic enzymes are produced by a variety of pathogenic microorganisms, and contribute to host colonization by modulating virulence. Here, we present a first characterization of leptolysin, a Leptospira metalloprotease of the pappalysin family identified in a previous exoproteomic study. Comparative molecular analysis of leptolysin with two other pappalysins from prokaryotes, ulilysin and mirolysin, reveals similarities regarding calcium, zinc, and arginine -binding sites conservation within the catalytic domain, but also discloses peculiarities. Variations observed in the primary and tertiary structures may reflect differences in primary specificities. Purified recombinant leptolysin of L. interrogans was obtained as a 50 kDa protein. The protease exhibited maximal activity at pH 8.0 and 37°C, and hydrolytic activity was observed in the presence of different salts with maximum efficiency in NaCl. Substrate specificity was assessed using a small number of FRET peptides, and showed a marked preference for arginine residues at the P1 position. L. interrogans leptolysin proteolytic activity on proteinaceous substrates such as proteoglycans and plasma fibronectin was also evaluated. All proteins tested were efficiently degraded over time, confirming the protease´s broad-spectrum activity in vitro. In addition, leptolysin induced morphological alterations on HK-2 cells, which may be partially attributed to extracellular matrix (ECM) degradation. Hemorrhagic foci were observed in the dorsal skin of mice intradermally injected with leptolysin, as a plausible consequence of ECM disarray and vascular endothelium glycocalyx damage. Assuming that leptospiral proteases play an important role in all stages of the infectious process, characterizing their functional properties, substrates and mechanisms of action is of great importance for therapeutic purposes.